2023
DOI: 10.1007/s11356-023-25288-y
|View full text |Cite
|
Sign up to set email alerts
|

How do vertical fiscal imbalances affect energy efficiency? The role of government spending on science and technology

Abstract: How to improve energy efficiency is a practical issue of common concern around the world. In China, vertical fiscal imbalances (VFIs) generated under the existing fiscal system may have a significant impact on energy efficiency through government spending on science and technology (S&T). However, this potential relationship has not been explored in the literature. In this work, we aim to address this gap. Using Chinese provincial panel data from 2001 to 2017, this study empirically examines the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Finally, in terms of research findings, our results validate the negative impact of VFI on GTFP and likewise reveal the institutional causes of the lack of incentive for the green transformation of the Chinese economy. This supports the study of Huang and Zhou,2020, and Feng, Liu, and Li, 2023 [28,55] to a certain extent and confirms Chen and Qi's, 2022 [56] view that the "governance" function of fiscal policy in China is under-represented. Furthermore, by introducing marketization indicators, our analysis confirms that VFI has a negative impact on economic and social development by distorting factor allocation (Cui, 2023) [57].…”
Section: Discussionsupporting
confidence: 82%
“…Finally, in terms of research findings, our results validate the negative impact of VFI on GTFP and likewise reveal the institutional causes of the lack of incentive for the green transformation of the Chinese economy. This supports the study of Huang and Zhou,2020, and Feng, Liu, and Li, 2023 [28,55] to a certain extent and confirms Chen and Qi's, 2022 [56] view that the "governance" function of fiscal policy in China is under-represented. Furthermore, by introducing marketization indicators, our analysis confirms that VFI has a negative impact on economic and social development by distorting factor allocation (Cui, 2023) [57].…”
Section: Discussionsupporting
confidence: 82%
“…2 ⃝ Numbers in parentheses are p-values; 3 ⃝ *** and ** denote the rejection of the null hypothesis at 1% and 5% significance levels, respectively, and I(n) denotes that the series is smooth after nth-order differencing. 4 ⃝ The data in this table were computed by Stata 17.0.…”
Section: Panel Unit Root Testmentioning
confidence: 99%
“…At the Central Economic Work Conference in December 2019, it was further pointed out that the economy should achieve reasonable quantitative growth and steady qualitative improvement, and it should strive to promote high-quality development [3]. General Secretary Xi Jinping stated in the report of the 20th Party Congress that it is necessary to accelerate the construction of a new development pattern and focus on promoting high-quality development, stressing that "all-round high-quality development is the essential job of constructing a modern socialist country" [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have analyzed the impact of LFP on separate sector efficiency, such as energy and green environmental efficiencies. Feng et al (2023) used Chinese provincial panel data from 2001 to 2017 in examining the relationship between vertical fiscal imbalances and energy efficiency through a mediation model [ 27 ]. Their results showed that vertical fiscal imbalances substantially suppress energy efficiency by reducing government spending on science and technology.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%